Biologics Therapy in Paediatric Rheumatic Diseases in Hong Kong - Winnie KY Chan; Assunta CH Ho; GPK Chiang; RHM Yeung; MCI Kuok; AOM Chan; MHC Lam; EYL Kwong (Journal of Clinical Rheumatology and Immunology)
Background: There is a substantial expansion in the number of biologics available for the treatment of JIA and childhood rheumatic disease over the past decades. However, there is no report on their use and safety profile in the local paediatric population. Method of study: This is a multi-centred retrospective cohort study, recruiting patients followed up in three Paediatric departments in Hong Kong. Subjects who were followed up for childhood-onset rheumatic diseases and was treated with any of the biologic DMARs on or before the 31st December 2022, were reviewed. Results: A total of 96 patients who received biologic DMARs in the studied period were reviewed. Sixty patients were diagnosed to have JIA, cSLE (10), uveitis (8), refractory KD (7), JDM (2), COVID-MISC (3), and others (6). Concerning the JIA group, male: female is 1.4:1. 38% of the patients had polyarticular JIA and 50% had ERA who failed conventional treatment with various cDMARS. Concerning the nature of biologics, 85% of JIA patients used different types of TNF-blockers, including etanercept (38.3%), adalimumab (40%), golimumab (5%) and infliximab (3.3%). Six JIA patients used tocilizumab and one used abatacept as second-line treatment after fail response to TNF-blockers. One JIA patient was on tofacitinib to avoid subcutaneous injection. For other biologics, infliximab for refractory KD (8), rituximab for cSLE and JDM (7 and 1), belimumab in cSLE (2) and anakinra in COVID-MISC (4). One JIA-ERA patient developed lymphoma six months after stopping adalimumab and recovered after chemotherapy. One cSLE patient received rituximab and developed EBV-related CNS lymphoma with repeated infections that required hospitalization. Most patients tolerated the biologic DMARs well without complications. There was no tuberculosis infection or activation. Two cSLE patients developed herpes zoster after rituximab infusion and required hospital treatment. Two patients on adalimumab developed recurrent folliculitis and one had to stop treatment. One patient developed bacteria endophthalmitis while on adalimumab. Four patients on adalimumab developed injection site reactions and one patient need to change to another biologic. One patient on adalimumab developed positive lupus serology without clinical features. Conclusion: A broad spectrum of biologics has been used in children with various rheumatic diseases without major complications. Although rare, 2 patients developed lymphoma during the study period. Although there is no causal relationship identified with the use of biologics, continuous monitoring of the long-term safety of these drugs in the paediatric cohort is recommended.